GROWTH AND EXPLOITATION STATUS (Channa striata Bloch, 1793) IN LUBUK LAMPAM FLOODPLAINS, SOUTH SUMATERA - Zulkarnaen Fahmi; Syarifah Nurdawati; Freddy Supriyadi (Indonesian Fisheries Research Journal, 2013)
Due to the economic importance of C. striata in Lubuk Lampam floodplains (Indonesia), this study is aimed to estimate the biological and population parameters required for proposing a future plan to sustain and manage this valuable fish resource. The growth, mortality and explotation ratio of Channa striata estimated by employing FiSATProgramme are reported. The parameters of Von Bertalanffy growth model of 1,529 sample fishes were estimated as K= 0.36/ year, L” = 72.98 cm and to = -0.52 year. The coefficients of total mortality (Z), natural mortality (M) and fishing mortality (F) were 1.72, 0.73 and 0.99 year-1 respectively. Relative yield per recruit analysis shows that the presentexploitation rate (E) was 0.58. Yield per recruit can be maximized at the exploitation ratio of 0.5 and Lc/Linf values of 0.3. The Yield per recruit and biomass per recruit models indicated that, the fisheries status of C. striata in Lubuk Lampam floodplains exceed the limit reference point (Fmax), thus stock of this species in Lubuk Lampam floodplains is indicated being driving down.Reduction in fishing effort and increase number of selective fishing gears are suggested to sustain the fishery of Channa striata in Lubuk Lampam floodplains.